Hermeneutika Alkitab Dalam Sejarah: Prinsip Penafsiran Alkitab Dari Masa ke Masa - Yohanes Verdianto (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2020)
The practice of hermeneutics has become an inseparable part of human history. Hermeneutics as human activity arises from the need to interpret thoughts or texts written by others. A historical search reveals that there have been some changes in the principles of biblical hermeneutics. This paper aims to find out what are the principles of hermeneutics that developed from the early church up to the postmodern era. This paper is a historical approach using documentary research method. The results of this study state that there are at least three principles of biblical interpretation from the early church to postmodern times. First, the literal hermeneutics of the Bible was agreed upon by all early church Fathers, although contextual, grammatical, and historical interpretation of the Bible was emphasized by two church Fathers, namely Theodore and Chrysostom. This literal hermeneutics was used until the reform era. Second, modern hermeneutics refers to reason rather than the literal principle. This is the emerge of hermeneutics of relativism which bases truth on the senses and reasons. This principle agrees the application of rationalism to the Bible which leads to historical-critical. Third, contemporary (postmodern) hermeneutics is more towards a process of understanding that is temporary. This means that understanding has no clear boundaries, and that interpreters cannot reach a fully certain understanding. Thus, contemporary biblical hermeneutics is full of subjectivism, relativism, pluralism and is temporary.